Respiratory system determinants of peripheral fatigue and endurance performance - Dempsey, J. A.; Amann, M.; Romer, L. M.; Miller, J. D. (Medicine & Science in Sports & Exercise, 2008)
We briefly summarize recent evidence pertaining to how mechanisms primarily under the control of the respiratory system-namely, arterial oxyhemoglobin desaturation, respiratory muscle work and fatigue, and cyclical fluctuations in intrathoracic pressure-may contribute to exercise limitation. Respiratory influences on cardiac output and on sympathetic vasoconstrictor activity and blood flow distribution are shown to be important determinants of performance. We also address how a compromised O2 transport exacerbates the rate of development of peripheral muscle fatigue and, in turn, precipitates central fatigue and exercise limitation.